Does Quran Memorization Influence Adolescents’ Intelligence Quotient and Memory Level?: A Cross-Sectional Study in Malaysia - Ishak, Ismarulyusda; Shaidin, Amira Aqilah; Harun, Dzalani; Abdul Warif, Nor Malia; Mariappan, Vanitha; Mat Ludin, Arimi Fitri; Ghazali, Ahmad Rohi; Ibrahim, Farah Wahida; Che Din, Normah (UI Scholars Hub, 2021)
Background: The process of memorizing various reading materials enhances the brain capacity to process, store, and assemble memories and increases the intelligence quotient (IQ) level. However, the connection between the memorization of Quran and the enhancement of memory level is not fully understood. Hence, a cross-sectional study was conducted to examine the correlation between Quran memorization and the IQ level among Muslim adolescents from selected Islamic schools in Selangor, Malaysia. Methods: The Wechsler Abbreviated Scale of Intelligence was used to measure the student’s IQ level, whereas Digit Span and Rey Auditory Verbal Learning Test were used to evaluate the memory level. Questionnaires were distributed for demographic data collection and the Quran memorization level. Results: The full-scale results for all the four sub-tests revealed that the studied tahfiz students had a low average level of IQ, with a mean of 88.06 ± 15.80. For the short-term verbal memory, the majority (n = 36, 56.3%) were in the normal category, whereby for long-term verbal memory, the majority (n = 20, 31.3%) were below normal. The results showed that the IQ level was non-significant (p = 0.059) but moderately correlated (r = 0.391) with the level of Quran memorization. The coefficient of determination or effect size calculation showed that Quran memorization shared 15.29% of the variability in the IQ level. Multiple linear regression analysis revealed that only the working memory is significant to predict the IQ. Provided that other influencing factors are constant, an increase of one unit in the working memory was predicted to increase 5.55 units of IQ. Conclusions: In conclusion, the level of Quran memorization was not significantly correlated with the IQ and memory status of Muslim adolescents from the selected Islamic schools in Selangor, Malaysia.